Arthrospira platensis Cultivation in a Bench-Scale Helical Tubular Photobioreactor - Alessandro Alberto Casazza; Ricardo Pinheiro de Souza Oliveira; Milena Fernandes da Silva; Carlo Solisio; Charles Bronzo Barbosa Farias; Leonie Asfora Sarubbo; Attilio Converti (Applied Sciences, 2022)
Cultivations of Arthrospira platensis were carried out to evaluate the CO2 capture capacity of this cyanobacterium under bench-scale conditions. For this purpose, the influence of light intensity on the microbial growth and the photosynthetic efficiency has been investigated in a helical photobioreactor. Five cultivations were performed at different photosynthetic photon flux densities (23 ≤ PPFD ≤ 225 µmol photons m−2 s−1) by fed-batch pulse-feeding pure carbon dioxide from a cylinder into the helicoidal photobioreactor. In particular, a range of PPFD (82–190 µmol photons m−2 s−1) was identified in which biomass concentration reached values (9–11 gDW L−1) significantly higher than those reported in the literature for other configurations of closed photobioreactors. Furthermore, as A. platensis suspensions behave as Newtonian and non-Newtonian (pseudoplastic) fluids at very low and high biomass concentrations, respectively, a flow analysis was carried out for evaluating the most suitable mixing conditions depending on growth. The results obtained in this study appear to be very promising and suggest the use of this helicoidal photobioreactor configuration to reduce CO2 emissions from industrial gaseous effluents.